2019
DOI: 10.1111/phpp.12462
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety profile for home NB‐UVB vs. outpatient NB‐UVB in the treatment of non‐segmental vitiligo: A prospective cohort study

Abstract: Summary Objective The aim of this study was to evaluate the efficacy and safety of home and outpatient narrowband ultraviolet B light (NB‐UVB) for the treatment of non‐segmental vitiligo. Methods A total of 94 patients with non‐segmental vitiligo were enrolled. Forty‐eight patients were treated with home NB‐UVB, and the other 46 patients were treated with outpatient NB‐UVB over a period of 6 months. The efficacy, patient quality of life, and adverse events were assessed at month 3 and month 6 after treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(39 reference statements)
0
14
0
Order By: Relevance
“…The findings of similar repigmentation efficacy, improvement in patient-reported quality of life, and higher rates of adverse events, were echoed in a recent systematic review of randomized control trials. 72 A prospective cohort study by Zhang et al 73 found that clinicbased NB-UVB generated better repigmentation rates compared to home-based NB-UVB after 3 months of treatment (p < 0.05), however, there was no significant difference in repigmentation rates between the two treatment modalities by 6 months of treatment:…”
Section: Efficacy and Adverse Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of similar repigmentation efficacy, improvement in patient-reported quality of life, and higher rates of adverse events, were echoed in a recent systematic review of randomized control trials. 72 A prospective cohort study by Zhang et al 73 found that clinicbased NB-UVB generated better repigmentation rates compared to home-based NB-UVB after 3 months of treatment (p < 0.05), however, there was no significant difference in repigmentation rates between the two treatment modalities by 6 months of treatment:…”
Section: Efficacy and Adverse Effectsmentioning
confidence: 99%
“…A prospective cohort study by Zhang et al 73 found that clinic‐based NB‐UVB generated better repigmentation rates compared to home‐based NB‐UVB after 3 months of treatment ( p < 0.05), however, there was no significant difference in repigmentation rates between the two treatment modalities by 6 months of treatment: 84% of patients experienced repigmentation in the home‐based NB‐UVB group, compared with 90% in the clinic‐based NB‐UVB group. In addition, subgroup analysis in the same study revealed that long‐standing vitiligo cases had a significantly better response to clinic‐based NB‐UVB compared to home‐based NB‐UVB.…”
Section: Home‐based Phototherapymentioning
confidence: 99%
See 1 more Smart Citation
“…This can be undertaken using either whole‐body units or handheld and non‐handheld devices for localized areas 33–36 . A prospective study showed no significant difference in repigmentation rates between home‐based and hospital‐based phototherapy, and only minimal adverse effects and similar health‐related quality‐of‐life scores 37 . A randomized controlled trial of home interventions (HI‐Light Vitiligo Trial) found that combination treatment with home‐based handheld NB‐UVB and potent topical corticosteroid was likely to be superior to potent topical corticosteroid monotherapy in the treatment of localized vitiligo 38 …”
Section: Improving Accessmentioning
confidence: 99%
“…[33][34][35][36] A prospective study showed no significant difference in repigmentation rates between home-based and hospital-based phototherapy, and only minimal adverse effects and similar health-related quality-of-life scores. 37 A randomized controlled trial of home interventions (HI-Light Vitiligo Trial) found that combination treatment with home-based handheld NB-UVB and potent topical corticosteroid was likely to be superior to potent topical corticosteroid monotherapy in the treatment of localized vitiligo. 38 It is important to recognize that there are increased safety concerns in the home setting that should be carefully considered.…”
Section: Improving Accessmentioning
confidence: 99%